2015
DOI: 10.15252/embj.201490784
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in malignant transformation and cancer progression

Abstract: Autophagy plays a key role in the maintenance of cellular homeostasis. In healthy cells, such a homeostatic activity constitutes a robust barrier against malignant transformation. Accordingly, many oncoproteins inhibit, and several oncosuppressor proteins promote, autophagy. Moreover, autophagy is required for optimal anticancer immunosurveillance. In neoplastic cells, however, autophagic responses constitute a means to cope with intracellular and environmental stress, thus favoring tumor progression. This imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
939
3
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 1,032 publications
(963 citation statements)
references
References 284 publications
(400 reference statements)
6
939
3
15
Order By: Relevance
“…today's consensus is that autophagy is a response to stress or damage. [63][64][65][66][67] Activation of autophagy serves to eliminate the damaged material and to generate extra energy, allowing a cell to survive a hopefully transient stress. If, in spite of this protection, the cell is too greatly stressed, it will undergo apoptosis.…”
Section: Open Questionsmentioning
confidence: 99%
“…today's consensus is that autophagy is a response to stress or damage. [63][64][65][66][67] Activation of autophagy serves to eliminate the damaged material and to generate extra energy, allowing a cell to survive a hopefully transient stress. If, in spite of this protection, the cell is too greatly stressed, it will undergo apoptosis.…”
Section: Open Questionsmentioning
confidence: 99%
“…4 Studies have shown that autophagy plays different or even opposite roles depending on the cancer type and the stage of tumor progression. Currently, it is generally accepted that autophagy behaves as a tumor suppressor in normal cells in part because it removes damaged cellular components.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…31 Autophagy is inhibited by oncogenic tyrosine kinases (OncTKs) and receptor tyrosine kinases (RTKs) via activation of the PI3K/AKT/mTORC1 and RAS/MAPK signalling. 37 In this respect, work from our group and others has shown that induction of autophagy upon pharmacological targeting of OncTKs/RTKs promotes survival. In turn, pharmacological inhibition of autophagy potentiates OncTK/RTK targeted therapy.…”
Section: Introductionmentioning
confidence: 99%